Decision making in frontotemporal dementia: neuropsychological and neuroimaging assessments - Tavakolan Haghighi, Shima; Bertasini, Chiara; Picari, Rozalda; Paolone, Giovanna (Frontiers in Neuroscience, 2025)
Frontotemporal dementia (FTD) is a neurodegenerative disorder primarily affecting the frontal and temporal lobes, leading to significant impairments in executive function, social behavior, and emotional regulation. FTD is clinically categorized into two variants, the behavioral (bvFTD) and the primary progressive aphasia (PPA). The bvFTD is the most common form of FTD, and, in these patients, impaired decision-making is the most prominent and clinically relevant cognitive deficit, often manifesting early and preceding more global cognitive decline. This narrative review explores the neuropsychological and neurobiological basis of decision-making deficits in FTD, with a focus on tasks such as the Moral Behavior Inventory (MBI), Iowa Gambling Task (IGT), Executive and Social Cognition Battery (ESCB), Addenbrooke’s Cognitive Examination (ACE), and the Balloon Analog Risk Task (BART). Evidence from both case and cohort studies reveals that, although bvFTD patients have intact cognitive profiles, they show impaired performance on decision-making tasks, suggesting that these deficits may be an early and specific marker of the disease. In addition, according to neuroimaging studies, these impairments are associated with atrophy in a distributed network, including the ventromedial and orbitofrontal cortices, anterior cingulate, insula, and even cerebellar regions. Finally, impaired decision-making is a critical yet underrecognized marker for early detection and differentiation of FTD from other forms of dementia.